Prospective observational evaluation of radiation-induced late taste impairment kinetics in oropharyngeal cancer patients: Potential for improvement over time?. (May 2020) - Stieb, Sonja; Mohamed, Abdallah S.R.; Deshpande, Tanaya S.; Harp, Jared; Greiner, Benjamin; Garden, Adam S.; Goepfert, Ryan P.; Cardoso, Richard; Ferrarotto, Renata; Phan, Jack; Reddy, Jay P.; Morrison, William H.; et al.
Highlights: The majority of OPC patients are affected from late taste impairment after RT. Taste markedly improved in the first years from end of RT, but plateaued after year 5. Treatment site, CTV1 dose and age might have an influence on taste impairment. Abstract: Background and purpose: Taste impairment is a common radiation-induced toxicity in head and neck cancer (HNC) patients acutely. However, data on the potential for recovery and the time dependent course of late taste impairment are limited. Materials and methods: As part of an IRB-approved observational prospective study, HNC patients underwent serial surveys including the MD Anderson Symptom Inventory - Head and Neck module (MDASI-HN). For our analysis, we extracted MDASI-HN taste item results from oropharyngeal cancer patients treated with intensity-modulated radiotherapy or volumetric modulated arc therapy and at least two taste assessments after ≥1 year from end of radiotherapy (RT). Results: 1214 MDASI taste items from 326 patients between 1 and 13 years post-RT were included. Median prescribed dose to the high-dose clinical target volume (CTV1) was 66.0 Gy, with 180 patients (55%) receiving chemotherapy. Taste markedly improved in the first years from end of RT, but plateaued after year 5. In patients with taste assessment in subsequent years, a significant reduction in taste impairment was found from the second to the third year (p = 0.001) and tended towards significance from the third to the fourth year (p = 0.058). Multivariate analysis revealed treatment site as significant factor in the sixth year from RT and CTV1 dose and age in the seventh year. Conclusion: Radiation-induced taste impairment may improve over an extended time interval, but becomes relatively stable from year 5 post-RT. Direct characterization of RT-induced taste impairment and the calculation of normal tissue complication probability should include consideration of the time-dependent course in taste recovery.